Audit Internal Pengelolaan Anggaran Disdukcapil dalam Pelayanan Administrasi Kependudukan di Surabaya - Muhammad Alvin Dewantoro; Daniel Billy Pratama; Aldhoni Putra Pradhana; Awwal Dyan Maulia; Synthia Aileen Firdausi Athallah W (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
Managing budgets in public institutions is not merely a matter of calculating numbers, but also about ensuring that every rupiah spent generates a tangible impact on society. As public needs continue to grow, the Department of Population and Civil Registration (Disdukcapil) of Surabaya faces significant challenges in providing administrative services that are fast, accurate, and transparent. In this context, internal audits play a strategic role not only as tools for correcting errors, but also in ensuring that budget management is carried out wisely and effectively. This study aims to examine the role of internal audits in the budget management of Disdukcapil and their contribution to improving the quality of public services. Using a descriptive qualitative approach, data were collected through documentation, interviews, and literature review. The findings are expected to provide a comprehensive overview of the relationship between internal oversight and the quality of public services in Surabaya.